Factor structure and psychometric properties of the modified childhood anxiety sensitivity index in a sample of Croatian children and adolescents - Jokić-Begić, Nataša; Lauri Korajlija, Anita; Jurin, Tanja (2012)
The Childhood Anxiety Sensitivity Index (CASI) is a well accepted operationalization of the AS construct in children and adolescents. This study evaluated the factor structure, gender stability and psychometric properties of the CASI, modified to a 5-point scale, in a sample of Croatian children and adolescents (N = 1, 679). Exploratory and confirmatory analysis and a Schmid-Leiman solution confirmed the multidimensional and hierarchical structure of the CASI, which consisted of three lower-order factors and a single higher-order factor. Further, the modification of the CASI to a 5-point scale resulted in higher reliability, while maintaining acceptable levels of factor stability and validity.
Projekt MZOS
ENG